Comparison of Incident of Chronic Pain Post Operations of Preperitoneal Transabdominal Herniorafi Laparoscopy (TAPP) and Totally Extraperitoneal (TEP) in General Hospital Dr. M. Djamil Padang - Yudi Ichsan Ramata; M.Iqbal Rivai; Avit Suchitra (Biomedical Journal of Indonesia, 2021)
Introduction : Inguinal herniation is a protrusion of peritoneal component through abdominal wall caused by the weakness of aponeurotica tissue of abdomen. Inguinal herniation is the most common herniation cases in which 291.145 patient registered in Indonesia at 2012 and 87 patients in General Government Hospital of M. Djamil Padang at 2017-2018. Herniation treatment is consisted of herniorrhapy laparoscopy using the TEP or TAPP techniques and both of them are related to the incidence of chronical post-operative pain that was defined by IASP as an uncomfortable sensation lasting for more than 3 months. Method: This research was using retrospective study design. The research was conducted at RSUP Dr. M. Djamil Padang in August – October 2020 with 54 samples. Result: The study found there was 54 cases of inguinal herniation fit to the inclusion criteria with peak age of 82 years old and average of 59.1 years old. Most patients were male (79.62 %). There were 2 patients having chronic pain (7.41%) after herniorrhapy using the TAPP technique and 1 more (3.71%) having chronic pain with TEP technique. Bivariate analysis was done by Fisher Exact Test and the study concluded there was no statistical significance in relationship of chronic post-operative pain incidence with the particular technique chosen at herniorrhapy laparoscopy (p=1.000). Conclusion:There was no significant relationship between the incidence of postoperative chronic pain in patients undergoing laparascopic hernioraphy and TEP or TAPP procedure.